2014
DOI: 10.1086/bblv227n1p78
|View full text |Cite
|
Sign up to set email alerts
|

The HMA-LMA Dichotomy Revisited: an Electron Microscopical Survey of 56 Sponge Species

Abstract: Abstract. The dichotomy between high microbial abundance (HMA) and low microbial abundance (LMA) sponges has been long recognized. In the present study, 56 sponge species from three geographic regions (greater Caribbean, Mediterranean, Red Sea) were investigated by transmission electron microscopy for the presence of microorganisms in the mesohyl matrix. Additionally, bacterial enumeration by DAPI-counting was performed on a subset of samples. Of the 56 species investigated, 28 were identified as belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
224
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(240 citation statements)
references
References 46 publications
12
224
2
2
Order By: Relevance
“…Previous studies have categorized H. heliophila as a low-microbial-abundance (LMA) sponge on the basis of transmission electronmicroscopic observations and microbial species composition (29,31). The latter is consistent with our results, as bacterial communities associated with LMA sponges tend to be dominated by Proteobacteria or Cyanobacteria (47,48). In addition, the phyla Planctomycetes, Cyanobacteria, and Deferribacteres were common members of the H. heliophila microbiome.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have categorized H. heliophila as a low-microbial-abundance (LMA) sponge on the basis of transmission electronmicroscopic observations and microbial species composition (29,31). The latter is consistent with our results, as bacterial communities associated with LMA sponges tend to be dominated by Proteobacteria or Cyanobacteria (47,48). In addition, the phyla Planctomycetes, Cyanobacteria, and Deferribacteres were common members of the H. heliophila microbiome.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, sponge tissue with this level of d 15 N would suggest N 2 fixation by the microbial symbionts (22,46). Accordingly, the high d 15 N values found for LMA sponges from the Florida Keys (46) suggest no or negligible N 2 fixation in these sponges, a finding which falls in line with our findings of high d 15 N levels and no measurable N 2 fixation in the Mediterranean LMA sponges. Of the sponges examined, only the HMA species C. reniformis showed a low d 15 N of 2‰, potentially indicating nitrogen import through N 2 fixation.…”
Section: Discussionsupporting
confidence: 85%
“…Sponges have been categorized as those with a high microbial abundance (HMA) and those with a low microbial abundance (LMA) (12), where HMA species harbor dense, diverse microbial communities and LMA species contain fewer and less diverse microorganisms (6,(13)(14)(15). Despite their distinct microbial compositions, HMA and LMA sponges show similar functional gene repertoires, which has been interpreted to be a functional convergence between the two microbiome types (10,11,16).…”
mentioning
confidence: 99%
“…The proteobacterial OTUs are dominated in adult A. queenslandica by classes Beta-and Gamma-proteobacteria, as observed in several species of low microbial abundance (LMA) sponge (Hentschel et al, 2003;Giles et al, 2012), rather than the more generally observed dominance by Gamma-and Alpha-classes (Thomas et al, 2016). Together, these observations indicate that A. queenslandica is appropriately considered as a LMA sponge species, as has been reported for congeners (Gloeckner et al, 2014;Poppell et al, 2014).…”
Section: Amphimedon Queenslandica Adults House a Low Complexity Microsupporting
confidence: 54%